Can Rare Events Explain the Equity Premium Puzzle? - Julliard, Christian; Ghosh, Anisha (Review of Financial Studies, 2012)
Probably not. First, allowing the probabilities of the states of the economy to differ from their sample frequencies, the consumption-CAPM is still rejected in both U.S. and international data. Second, the recorded world disasters are too small to rationalize the puzzle, unless one assumes that disasters occur every 6–10 years. Third, if the data were generated by the rare events distribution needed to rationalize the equity premium puzzle, the puzzle itself would be unlikely to arise. Fourth, the rare events hypothesis, by reducing the cross-sectional dispersion of consumption risk, worsens the ability of the consumption-CAPM to explain the cross-section of returns. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.